The Effectiveness of Spiritual-Based Cognitive Behavior Therapy (CBT) on Depression of Leprosy Patients - Endang Fauziyah; Nur Iszakiyah; Kuzzairi Kuzzairi (University of Muhammadiyah Malang, 2022)
Introductions: The decrease in depression in leprosy patients using Spiritual-based Cognitive Behavior Therapy shows progressive results. Objectives: This study aimed to determine the effectiveness of spiritual-based Cognitive Behavior Therapy on the level of depression of leprosy patients at the Waru Health Centre, Pamekasan Regency. Methods: This research design was Quasi-Experiment Design with a pre-test – post-test group. Respondents consisted of 12 people who received spiritual-based CBT therapy. Spiritual-based CBT therapy was given in 3 sessions in 3 meetings. Data collection by filling out the DASS questionnaire pre- and post-spiritual-based CBT therapy interventions. Data was collected using the triangulation method, namely in-depth interviews (depth interviews) face to face with observations and scales. Results: The results showed that from the interpretation of the analysis results using the Paired T-Test statistical test, it was known that in the test before and after treatment, the value of p = 0.000 at the significance level of p = 0.05 (α = 0.05). When compared with the level of significance, which is 0.000 < 0.05, it can be concluded that there is an influence on the application of spiritual-based cognitive behavior therapy to people with leprosy who experience depression. Conclusions: Through cognitive restructuring techniques, participants' distorted cognitions become more rational. Participants can accept their condition and reduce negative thoughts that cause depression.